Atlas of hybrid imaging of the brain and neck. Sectional anatomy for PET/CT, PET/MRI and SPECT/CT / Volume 1, (2022) - Leporace, Mario; Calabria, Ferdinando; Gaudio, Eugenio; Schillaci, Orazio; Ciaccio, Alfonso; Bagnato, Antonio
No abstract available